Dislocation-Actuated Growth and Inhibition of Hexagonal L-Cystine Crystallization at the Molecular Level - Shtukenberg, A.; Poloni, L.; Zhu, Z.; An, Z.; Bhandari, M.; Song, P.; Rohl, Andrew; Kahr, B.; Ward, M. (American Chemical Society, 2015)
Crystallization of L-cystine is a critical process in the pathogenesis of kidney stone formation in cystinuria, a disorder affecting more than 20 000 individuals in the United States alone. In an effort to elucidate the crystallization of L-cystine and the mode of action of tailored growth inhibitors that may constitute effective therapies, real-time in situ atomic force microscopy has been used to investigate the surface micromorphology and growth kinetics of the {0001} faces of L-cystine at various supersaturations and concentrations of the growth inhibitor L-cystine dimethylester (CDME). Crystal growth is actuated by screw dislocations on the {0001} L-cystine surface, producing hexagonal spiral hillocks that are a consequence of six interlacing spirals of anisotropic molecular layers. The high level of elastic stress in the immediate vicinity around the dislocation line results in a decrease in the step velocities and a corresponding increase in the spacing of steps. The kinetic curves acquired in the presence of CDME conform to the classical Cabrera–Vermilyea model. Anomalous birefringence in the {101̅0} growth sectors, combined with computational modeling, supports a high fidelity of stereospecific binding of CDME, in a unique orientation, exclusively at one of the six crystallographically unique projections on the {1010} plane.